Hubungan Antara Karakteristik Keluarga dengan Tingkat Literasi Finansial Anak Usia Dini - Alfianti Arini G; Euis Kurniati; Fakhita Indira Haris; Nurcita Apsari; Salsabila Khoerunnisa; Tiara Lisania Sidqia; Aida Fitri Shofia; Ainnun Ibrahim Hamid (Universitas Muhammadiyah Surakarta, 2026)
Introducing financial literacy from an early age is increasingly important in response to rising consumptive behavior and financial risks among younger generations. This study aims to examine the relationship between early childhood financial literacy and family background, including parents’ occupations, parents’ educational levels, and children’s allowance. The study was conducted with 94 children from Group B in three early childhood education centers (PAUD) in Wanasaba District, East Lombok. Data were collected through observations and questionnaires, and analyzed using descriptive statistics and Spearman correlation tests. The results indicate that children’s financial literacy is categorized as “moderate,” with the highest scores found in the attitude dimension. No significant relationships were found between financial literacy and parents’ occupations (ρ = −0.202), parents’ educational levels (ρ = −0.044), or children’s allowance (ρ = 0.119). These findings highlight the importance of practice-based and habituation-oriented financial literacy learning strategies, implemented through collaboration between early childhood education institutions and families.